The International Encyclopedia of Primatology 2016
DOI: 10.1002/9781119179313.wbprim0045
|View full text |Cite
|
Sign up to set email alerts
|

Primates (Taxonomy)

Abstract: After spelling out the rationale for taxonomy, an annotated classification of living primates is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Africa is home to several species of NHPs (Groves, 2016;Grubb et al, 2003), with 25 genera and 94 species (De Jong and Butynski, 2012a). East Africa supports 68% of Africa's primate genera and 41% of Africa's primate species.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Africa is home to several species of NHPs (Groves, 2016;Grubb et al, 2003), with 25 genera and 94 species (De Jong and Butynski, 2012a). East Africa supports 68% of Africa's primate genera and 41% of Africa's primate species.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The two subspecies classification was the norm for only 4 years when Dandelot (1974) challenged this taxonomy, reclassifying C. a. sharpei as synonymous with C. a. palliatus, considering the pelage differences local adaptations. Dandelot's one subspecies classification, C. a. palliatus, remained the dominant, accepted taxonomy (Groves, 2001;Kingdon et al, 2008) even though Hull (1979) found species-level differences when 76 craniometric points were compared between the two populations.…”
Section: Introductionmentioning
confidence: 99%
“…Procolobus consists of the single olive colobus species, Procolobus verus, and while some authors consider the red colobus a subgenus (Grubb et al, 2013;Oates, 1994) or subspecies of Procolobus (Ting, 2008), others have elevated red colobus to their own genus, Piliocolobus (Groves, 2001(Groves, , 2007Roos et al, 2011). Taxonomic relationships of these genera remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The common marmoset ( C jacchus ) belongs to the order Primates , family Cebidae and subfamily Callitrichinae , and is most known and common in adaptation to captivity. They occupy the biomass of the caatinga, cerrado, and costal Atlantic Rainforest in Northeastern Brazil, in the states of Alagoas, Pernambuco, Paraíba, Sergipe, Rio Grande do Norte, Ceará, Maranhão, Bahia and Piauí, and extend south to the São Francisco river…”
Section: Introductionmentioning
confidence: 99%